(3GdJfejI GdGbJUGOjI aj GdJKHjJ hGdGUdGM hGdJcjja GdGbJUGOjs - (3VjGA eLjO(B, (3GdehShjs ((3GdCHjGQ(B-(3GdLRGFQ(B:s (3cfhR GdMceI(B,s, 2015)
(3GMJhi gPG GdcJGH Ydi SHYI aUhd JfGhdJ EUdGM GdSjGSGJ GdGbJUGOjI hSjGSI GSJgOGa GdJVNe, hVHW GdhVGY GdeGdjI, ceG Hqjf OhQ UfOhb GdfbO GdOhdj hGdEUdGMGJ GdgjcdjI aj GdGbJUGO, hOhQ GdJLGQI GdNGQLjI aj GdJcjja Gdgjcdj hJLGQH HYV GdMcheGJ aj GdJKHjJ hGdJcjja hGdEUdGM hGdGbJUGO Gdgjcdj, hCNjQG JfGhd GdJYOjd Gdgjcdj ddGbJUGO GdLRGFQj(B. s
Keywords: (3GdJLGQI GdNGQLjIs; (3GdJfejI GdGbJUGOjIs